PTU-016 Bolus intravenous proton-pump inhibitors as good as infusions post endoscopic treatment of high risk ulcers. (8th June 2018) - Wheatley, Daniel; Napier, Duncan; Terry, Leela; Main, Sean; Brooklyn, Trevor
Abstract : Introduction: Meta-analysis evidence suggests that IV boluses of proton pump inhibitors (PPIs) are non-inferior to IV infusions post endoscopic treatment of high risk peptic ulcers in terms of re-bleed rates. 1 Our trust guideline for PPI use post treatment of high risk ulcers was changed from IV infusion to IV bolus therapy. We have compared re-bleed rates for those treated with bolus therapy and those who were given infusions in line with the older guideline to see if real-world data from a UK DGH reflects the findings of the meta-analysis. Methods: All endoscopy reports (electronically captured at the time of endoscopy) for the six month periods prior to and after the change in guidelines were retrospectively reviewed. Once patients who had been treated for high risk ulcers were identified, the method of PPI administration they received, as well as their re-bleed rates were compared. A Chi-squared test was performed using SPSS. Results: The re-bleed rate prior to the change in guidelines was 14% (9 of 64) and after the change this fell to 10% (7 of 70) though the difference was not statistically significant (p-value 0.53). Conclusions: Our real-world data mirror the current evidence from the meta-analyses; we found no deleterious effects from switching to IV bolus PPI as adjuvant treatment in high risk peptic ulcer disease that has been treated endoscopically. We recommend switching to from PPI infusions to IV boluses which has cost and nurse time advantages while maintaining efficacy. Reference: . Sachar H, Vaidya K, Laine L. Intermittent vs continuous proton pump inhibitor therapy for high-risk bleeding ulcers: a systematic review and meta-analysis. JAMA Intern Med. 2014Nov;174(11):1755–62. doi:10.1001/jamainternmed.2014.4056